The closest lineage of Archaeplastida is revealed by phylogenomics analyses that include Microheliella maris. Issue 4 (13th April 2022) - Yazaki, Euki; Yabuki, Akinori; Imaizumi, Ayaka; Kume, Keitaro; Hashimoto, Tetsuo; Inagaki, Yuji
Abstract : Abstract : By clarifying the phylogenetic positions of 'orphan' protists (unicellular micro-eukaryotes with no affinity to extant lineages), we may uncover the novel affiliation between two (or more) major lineages in eukaryotes. Microheliella maris was an orphan protist, which failed to be placed within the previously described lineages by pioneering phylogenetic analyses. In this study, we analysed a 319-gene alignment and demonstrated that M. maris represents a basal lineage of one of the major eukaryotic lineages, Cryptista. We here propose a new clade name 'Pancryptista' for Cryptista plus M. maris . The 319-gene analyses also indicated that M. maris is a key taxon to recover the monophyly of Archaeplastida and the sister relationship between Archaeplastida and Pancryptista, which is collectively called 'CAM clade' here. Significantly, Cryptophyceae tend to be attracted to Rhodophyta depending on the taxon sampling (ex., in the absence of M. maris and Rhodelphidia) and the particular phylogenetic 'signal' most likely hindered the stable recovery of the monophyly of Archaeplastida in previous studies.